SYARIâAH: ANTARA KODIFIKASI HUKUM DAN MORAL ISLAM (Telaah Pemikiran Muhammad Saâid al-Ashmawi) - Yaqin, Haqqul (Humanistika : Jurnal Keislaman, 2015)
In the discourse of Islamic thought, Shariah is the word that was problematic and debatable. Most scholars agree that the sharia law contains a benefit for mankind. But they differed in putting welfare as an objective of sharia law. While Muhammad Said al-Ashmawi view based domination and motives "politicization of Islam" behind the growing phenomenon around the Sharia. For him, Shariah is not present in empty space, syariah manifests because there locus and tempos that has a specific make appropriate where the concept coined. In the context of Egypt, Ashmawi see obscurity theological foundation of a strong desire application of Shariah. Indeed, it is more pronounced is the scent of political Islam.